2020
DOI: 10.11628/ksppe.2020.23.3.293
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Locational Types and Biodiversity in the Sites of Geumgang Riparian Ecological Belts

Abstract: Background and objective: This study was carried out to assess the relationship between the internal and external environments and the ecological items in five sites with a high level of artificial use intensity prior to the establishment of Geumgang River riparian ecological belts. Methods: The sites were classified into forest type, cultivated land type and urbanized type in accordance with their respective locational types. Ecological items including plant ecology such as proportion, naturalization index an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…In other words, naturality was high in Jik-dong or Sangjang-ri located in lands adjacent to a forest. This is consistent with the result that the ratio of native species in areas near forests is higher than that of cultivated lands or lands adjacent to urbanized areas (Kang, 2020) or that the mountain type increases autogenous property and promotes habitat functionality (Son et al, 2014).…”
Section: Plant Ecologysupporting
confidence: 90%
See 4 more Smart Citations
“…In other words, naturality was high in Jik-dong or Sangjang-ri located in lands adjacent to a forest. This is consistent with the result that the ratio of native species in areas near forests is higher than that of cultivated lands or lands adjacent to urbanized areas (Kang, 2020) or that the mountain type increases autogenous property and promotes habitat functionality (Son et al, 2014).…”
Section: Plant Ecologysupporting
confidence: 90%
“…As a result of analyzing the correlation between internal/external environmental factors and ecological items of the sites (Table 5), it was found that the site area and planting area as the internal environment showed a negative correlation with the number of species of dragonfly species (r = -0.860, r = -0.922) and the number of amphibian and reptile individuals (r = -0.899, r = -0.939). This is similar to the result that planting areas like orchards have a more negative effect on inhabitation of dragonflies and amphibians than wetlands (Kim et al, 2018 In other words, areas with higher artificial use intensity had more negative effect on naturality, ecological property, and species diversity (Kang, 2020). As for the sites in this study, there was a negative effect on inhabitation of amphibians and reptiles as well as mammals.…”
Section: Correlation Between the Location Environment And Ecological Status Of The Research Sitessupporting
confidence: 85%
See 3 more Smart Citations